2021
DOI: 10.3386/w28782
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Run Spillover Effects of Pollution: How Exposure to Lead Affects Everyone in the Classroom

Abstract: The version presented here is a Working Paper (or 'pre-print') that may be later published elsewhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Health and safety bonds have the second largest impact at 0.15 sd, in line with recent findings on the negative consequences of toxic materials in schools (such as lead or asbestos) on students' cognitive outcomes (Sorensen et al, 2019;Gazze et al, 2021;Ferrie et al, 2012). Bonds that fund renovations of plumbing systems, roofs, furnaces, and STEM equipment also have a sizable test score impact, equal to 0.15 sd.…”
Section: Category-specific Impacts Of Bond Authorizationsupporting
confidence: 77%
“…Health and safety bonds have the second largest impact at 0.15 sd, in line with recent findings on the negative consequences of toxic materials in schools (such as lead or asbestos) on students' cognitive outcomes (Sorensen et al, 2019;Gazze et al, 2021;Ferrie et al, 2012). Bonds that fund renovations of plumbing systems, roofs, furnaces, and STEM equipment also have a sizable test score impact, equal to 0.15 sd.…”
Section: Category-specific Impacts Of Bond Authorizationsupporting
confidence: 77%
“…Further study would benefit from focusing on the efficacy of rehabilitation activities as well as whether the adverse outcomes persist over the long run. Previous work has also suggested that boys may have a larger response to lead exposure than girls (Khanna (2015), Reyes (2015), Gazze et al (2021)). Disaggregating the information by gender may also provide new and important insights.…”
Section: Discussionmentioning
confidence: 94%
“…Previous work has also suggested that boys may have a larger response to lead exposure than girls (Khanna (2015), Reyes (2015), Gazze et al. (2021)). Disaggregating the information by gender may also provide new and important insights.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, differences in school contexts are intertwined with the effects of environmental hazards. For example, a recent study showed that higher concentrations of lead‐poisoned children in a school are linked with a greater number of class disruptions, generating negative spillovers for other students (Gazze et al, 2021).…”
Section: The Developmental Effects Of Subclinical Lead Toxicitymentioning
confidence: 99%